Natural compounds target programmed cell death (PCD) signaling mechanism to treat ulcerative colitis: a review - Chen, Bo; Dong, Xinqian; Zhang, Jin Long; Sun, Xitong; Zhou, Lin; Zhao, Kangning; Deng, Hualiang; Sun, Zhen (Frontiers in Pharmacology, 2024)
Ulcerative colitis (UC) is a nonspecific inflammatory bowel disease characterized by abdominal pain, bloody diarrhea, weight loss, and colon shortening. However, UC is difficult to cure due to its high drug resistance rate and easy recurrence. Moreover, long-term inflammation and increased disease severity can lead to the development of colon cancer in some patients. Programmed cell death (PCD) is a gene-regulated cell death process that includes apoptosis, autophagy, necroptosis, ferroptosis, and pyroptosis. PCD plays a crucial role in maintaining body homeostasis and the development of organs and tissues. Abnormal PCD signaling is observed in the pathological process of UC, such as activating the apoptosis signaling pathway to promote the progression of UC. Targeting PCD may be a therapeutic strategy, and natural compounds have shown great potential in modulating key targets of PCD to treat UC. For instance, baicalin can regulate cell apoptosis to alleviate inflammatory infiltration and pathological damage. This review focuses on the specific expression of PCD and its interaction with multiple signaling pathways, such as NF-κB, Nrf2, MAPK, JAK/STAT, PI3K/AKT, NLRP3, GPX4, Bcl-2, etc. to elucidate the role of natural compounds in targeting PCD for the treatment of UC. This review used (ulcerative colitis), (programmed cell death) and (natural products) as keywords to search the related studies in PubMed and the Web of Science, and CNKI database of the past 10 years. This work retrieved 72 studies (65 from the past 5 years and 7 from the past 10 years), which aims to provide new treatment strategies for UC patients and serves as a foundation for the development of new drugs.